The Effectiveness of Picture Exchange Communication System on Behavioral Problems of Children with Autism - Maryam Mamaghanieh; Hamid Reza Pour-Etemad; Fatemeh Ahmadi; Katayoun Khoushabi (University of Social Welfare and Rehabilitation Sciences, 2011)
Objective: Autism is one the most disturbing neurodevelopmental disorders associated with variety behavioral problems including communication deficits. The present study is aimed to examine the effectiveness of the Picture Exchange Communication System (PECS) on behavioral problems of autistic children. Materials & Methods: This study follows a quasi- experimental single subject A-B design. Four boys with autism (aged between 3-7 years) were selected from the Center for the Treatment of Autistic Disorders, Tehran. They were received PECS training for duration of four months (42 session), three sessions per week. Direct observation assessment and Autism Treatment Evaluation Checklist were applied 6 times during the course of the study. Results: Separate set of analysis of the data reveled a positive effects of PECS on reduction of behavioral problems in three children, although, some differences were identified between them. Conclusion: Enhanced ability to communicate by PECS, would effectively reduce behavioral problems of children with Autism